2000
DOI: 10.1302/0301-620x.82b4.0820499
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinematics of total knee arthroplasty

Abstract: We studied the kinetics of the knee in 20 patients (22 knees) 12 months after total knee arthroplasty (TKA), by using three-dimensional radiostereometry and film-exchanger techniques. Eleven knees had a concave (constrained) tibial implant and 11 a posterior-stabilised prosthesis. Eleven normal knees served as a control group.In the posterior-stabilised knees there was less proximal and posterior displacement of the centre of the tibial plateau during extension from 45° to 15°, with a decrease in the anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Pre-operative tibial rotation during flexion was comparable to passive kinematic data of OA knees reported in [6,31,33,34] where magnitudes of tibial axial rotation are reduced in OA knees compared to normal knees [27,29,30,33]. After surgery, no significant reduction of tibial axial rotation was found, and this result is in contrast to the literature where a reduction of rotation was observed in TKA [22,33,36,41], except for the works of Stiehl et al [34] and Casino et al [6], where no significant reduction was found, or for Baier et al [1] who found that axial rotation increased after TKA. In the present study, all three implants had a lateral compartment translation range similar to pre-operative conditions, while the medial compartment presented a greater translation with respect to pre-operative condition and in extension, it was in a more anterior position.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Pre-operative tibial rotation during flexion was comparable to passive kinematic data of OA knees reported in [6,31,33,34] where magnitudes of tibial axial rotation are reduced in OA knees compared to normal knees [27,29,30,33]. After surgery, no significant reduction of tibial axial rotation was found, and this result is in contrast to the literature where a reduction of rotation was observed in TKA [22,33,36,41], except for the works of Stiehl et al [34] and Casino et al [6], where no significant reduction was found, or for Baier et al [1] who found that axial rotation increased after TKA. In the present study, all three implants had a lateral compartment translation range similar to pre-operative conditions, while the medial compartment presented a greater translation with respect to pre-operative condition and in extension, it was in a more anterior position.…”
Section: Discussionsupporting
confidence: 73%
“…Pre‐operative tibial rotation during flexion was comparable to passive kinematic data of OA knees reported in literature (range 4.9°–12.1°) [6, 31, 33, 34] where magnitudes of tibial axial rotation are reduced in OA knees compared to normal knees [27, 29, 30, 33]. After surgery, no significant reduction of tibial axial rotation was found, and this result is in contrast to the literature where a reduction of rotation was observed in TKA [22, 33, 36, 41], except for the works of Stiehl et al [34] and Casino et al [6], where no significant reduction was found, or for Baier et al [1] who found that axial rotation increased after TKA.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Acknowledging these limitations, the results of this study are consistent with the experimental work of the current and other authors [11,17,[20][21][22][23][24]27,34,38], where contemporary pivoting, fixed-bearing TKA designs have failed to reproduce normal knee kinematics [43]. On the other hand, the TKA pivoting design evaluated in this study and other dual-pivoting designs studied by different authors have demonstrated bettercontrolled kinematics that are correlated to better active flexion [23] and better functional muscle coordination [44,45], favoring clinically detectable improved knee stability.…”
Section: Discussionsupporting
confidence: 87%
“…Analyzing skeletal kinematics with radiostereometric analysis (RSA) following corrective orthopedic surgery allows the quantitative comparison of joints with different implant designs (Uvehammer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%